Challenges and Rewards Associated with Service-Learning in International Contexts: Pre-Service Teacher Outcomes - Miller, Kari Knutson; Gonzales, Amber M. (International Journal of Research on Service-Learning in Teacher Education, 2011)
This paper examines outcomes associated with the international (China) service-learning experiences of U.S. pre-service teachers. Quantitative and qualitative measures were used to assess participant perspectives before and at the conclusion of the course and its associated service-learning experience. Results suggest the international service-learning experience significantly contributes to both professional and personal development outcomes. Participants reported initial site-based experiences were particularly challenging. At the conclusion of their service-learning experiences, they reported positive impacts on their understandings of and abilities to apply course content, development of professional skills and strategies, and development of cultural competencies including knowledge and dispositions related to effective interaction with linguistically and culturally diverse children. Furthermore, participants reported enhanced confidence and stress and coping skills. Pre-service teacher recommendations for successful international service-learning experiences as well as recommendations for future research studies are offered.